«Revolutionary аttitude» in the context of the system-synergistic approach (M. Azuela «The Underdogs», I. Babel «Red Cavalry») - Садовська, Юлія Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The present article is devoted to the expediency of using a system-synergistic approach to M. Azuela and I. Babel’s works. Thus, the novels «The Underdogs», (M. Azuela) and «Red Cavalry» (I. Babel), devoted to the revolution and civil war, are to explore within the framework of the synergistic concept of chaos. Nowadays synergetics is beyond the scope of its primary attraction field and the expediency of this method in the humanitarian knowledge puts it in the category of the latest paradigms of modern science. Such an approach allows making a research at the interdisciplinary level, that is, due to the «cooperative effect» to reveal the general nature of the world perception. One of the main contradictions underlying the synergistic approach is the dialectical unity of order and chaos in the process of system existence. During the time of social, political and economic changes the dynamics of systems contains an increasing share of uncertainty (periods of chaotic behavior). Significantly, the revolutionary impulse depicted in M. Azuela’s work «The Underdogs» and I. Babel’s «Red Cavalry», is the stage of bifurcation, but the chaos created near the bifurcation point does not mean that the order disappears; it means that the process dynamics becomes unpredictable. The existing system goes into a stage of crisis, characterized by a violation of stability and imbalance. In M. Azuela’s work it is a spontaneous struggle of one of the revolution detachments, in I. Babel’s work – reality, covered by the chaos of the civil war. The person, who is immersed in a situation of chaos, is pursued with multi-vector and ambiguity of decisions. The process of choosing a path (attractor) is related to internal searches, and the solution is the result of doubt and contradiction. It is proved that this method of analysis makes it possible to show dissipative processes in a nonlinear environment and to recreate the patterns of behavior of the character in the situation of transition from order to chaos and vice versa. The patterns of characters’ behavior at the stage of the bifurcation are revealed in two hypostases: the chaos of reality (meaningless destruction, cruelty, aggression); the chaos of ideology and morals («confused person», experiencing a «breakdown of consciousness»).